Astaxanthin attenuates DNA fragmentation and cognitive decline in type 2 diabetic rats - Sohair A. Saleh; Gergess S. Hanna; Sobhy H. El-Naby; Suzy F. Ewida; Rasha S. A. Elseadawy; Basma S. Ghoneim; Shaimaa M. Motawea (Scientific Reports)
Abstract Potential properties of astaxanthin include immunomodulation, antioxidant, and anti-inflammatory effects. In diabetic rats, we examined the potential impacts and underlying mechanisms of astaxanthin on hippocampal DNA, cognition, and glycemic status. Rats were divided into five equal groups: non-diabetic, and diabetic (non-treated, metformin treated, astaxanthin treated, and treated with a combination of metformin and astaxanthin). Both spatial and non-spatial memory and learning were assessed. IL-6, malondialdehyde, total antioxidant capacity, lipid profile, and glycemic status were assessed. Phosphorylated tau expression level was measured, and H&E section analysis was used to evaluate the hippocampal tissue. DNA fragmentation, intact DNA, and hippocampal RNA were evaluated. Induction of diabetes led to a reduction in cognitive abilities along with significant hyperglycemia, dyslipidemia, oxidative stress, hyperphosphorylation of tau, and DNA fragmentation. Astaxanthin as monotherapy or in combination with metformin improved cognitive functions with reduction of hyperglycemia, dyslipidemia, oxidative stress, hyperphosphorylation of tau, and DNA fragmentation.